Menstrual cycle and competitive bidding - Matthew Pearson; Burkhard C. Schipper (University of California, Department of Economics, 2009)
In an experiment using two-bidder first-price sealed bid auctions with symmetric independent private values, we collected information on the female participants' menstrual cycles. We find that women bid significantly higher than men in their menstrual and premenstrual phase but do not bid significantly different in other phases of the menstrual cycle. We suggest an evolutionary hypothesis according to which women are genetically predisposed by hormones to generally behave more riskily during their fertile phase of their menstrual cycle in order to increase the probability of conception, quality of offspring, and genetic variety. It is in contrast to results by Chen, Katuscak and Ozdenoren (2005, 2009).
Keywords: C72; C91; C92; D44; D81; D87; 330; hormones; menstrual cycle; gender; likelihood of conception; first price auction; risk behavior; competition; bidding; endocrinological economics